2023
DOI: 10.3390/biomedicines11102797
|View full text |Cite
|
Sign up to set email alerts
|

Obesity-Associated Non-T2 Mechanisms in Obese Asthmatic Individuals

Harshita Shailesh,
Ajaz A. Bhat,
Ibrahim A. Janahi

Abstract: Obesity and asthma are two common health issues that have shown increased prevalence in recent years and have become a significant socioeconomic burden worldwide. Obesity increases asthma incidence and severity. Obese asthmatic individuals often experience increased exacerbation rates, enhanced airway remodeling, and reduced response to standard corticosteroid therapy. Recent studies indicate that obesity-associated non-T2 factors such as mechanical stress, hyperinsulinemia, systemic inflammation, adipose tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 90 publications
0
6
0
Order By: Relevance
“…As stated before, metabolic syndrome and insulin resistance are associated with increased risk of developing asthma and asthma severity. Hyperinsulinemia may promote airway smooth muscle airway hyperreactivity [71,72]. Medications targeting the metabolic syndrome and hyperglycemia may improve asthma morbidity.…”
Section: Targeting Metabolic and Glycemic Dysfunctionmentioning
confidence: 99%
“…As stated before, metabolic syndrome and insulin resistance are associated with increased risk of developing asthma and asthma severity. Hyperinsulinemia may promote airway smooth muscle airway hyperreactivity [71,72]. Medications targeting the metabolic syndrome and hyperglycemia may improve asthma morbidity.…”
Section: Targeting Metabolic and Glycemic Dysfunctionmentioning
confidence: 99%
“…Body mass index (BMI, kg/m 2 ) is calculated as weight divided by height squared, while fat mass index (FMI, kg/m 2 ) is calculated as fat mass divided by height squared. The Fat-free mass index (FFMI, kg/m 2 ) is calculated by dividing the sum of total lean mass and bone mineral content by the square of height [9,14,15].…”
Section: Assessmentmentioning
confidence: 99%
“…One review reported a 20% increase and a twofold increase in asthma's prevalence in overweight and obese children, respectively [4], while another review reported a 20% and a 40% risk increment in overweight and obese children, respectively [5]. Obesity-related factors such as altered lung mechanics, hyperinsulinemia, increased inflammation, metabolic dysregulation, and microbiome dysbiosis are implicated in the pathogenesis of asthma [9,10].…”
Section: Introductionmentioning
confidence: 99%